Nondestructive Evaluation 4.0: Ultrasonic Intelligent Nondestructive Testing and Evaluation for Composites. Issue 5 (1st November 2020) - Liu, Songping; Liu, Feifei; Yang, Yusen; Li, Legang; Li, Zhiying
ABSTRACT: With the continuous promotion of Industry 4.0, the mass production of composites will be entering Industry 4.0 in the near future. With respect to quality control, nondestructive testing and evaluation (NDT&E) will become nondestructive testing and evaluation (NDE) 4.0 to seamlessly connect with Industry 4.0. Therefore, it is essential to develop innovative NDT&E methods and techniques for NDE 4.0. Although there are many facets of NDE 4.0, intelligent nondestructive testing and evaluation (iNDT&E) can be considered as a technical core of NDE 4.0. Therefore, we propose the development of iNDT&E techniques for composites. In this study, the development processes for NDE 1.0–4.0 are analyzed. The basic connotations of iNDT&E are discussed, and the basic framework and technical elements of iNDT&E are examined. As combined with ultrasonic iNDT&E for composites, the basic progress in iNDT&E techniques is reviewed from the perspectives of ultrasonic equipment, technology and methods, processes, and result evaluations and standards. Future development directions are presented for the iNDT&E techniques in NDE 4.0 for composites.